Abraham Acosta. Thresholds of Illiteracy: Theory, Latin America, and the Crisis of Resistance. New York: Fordham UP, 2014. xiv + 276 pp. - Miguel Gonzalez-Abellas (Studies in 20th & 21st Century Literature, 2015)
Review of Abraham Acosta. Thresholds of Illiteracy: Theory, Latin America, and the Crisis of Resistance. New York: Fordham UP, 2014. xiv + 276 pp.
Keywords: Latin America; orality; literacy; illiteracy; subaltern; resistance